2020
DOI: 10.1039/d0ta03809a
|View full text |Cite
|
Sign up to set email alerts
|

Multiple diffusion pathways in LixNi0.77Co0.14Al0.09O2 (NCA) Li-ion battery cathodes

Abstract: Experimental evidence for the presence of two diffusion pathways, namely the oxygen dumbbell hop (ODH) and tetrahedral site hop (TSH), has been given for the first time by muon spin relaxation (µSR) in layered oxide lithium ion battery cathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…It is observed that as temperature increases there is a corresponding decrease in the eld distribution width due to Li + diffusion becoming more rapid and leading to a motional narrowing effect similar to that seen in previous investigations. 26,42 As [Ni] increases (and thus, [Mn] and [Co] decreases) there is a consistent decrease in D due to the signicantly smaller nuclear moment present in Ni, when compared to Mn or Co.…”
Section: Local Lithium Diffusion (Msr)mentioning
confidence: 89%
See 3 more Smart Citations
“…It is observed that as temperature increases there is a corresponding decrease in the eld distribution width due to Li + diffusion becoming more rapid and leading to a motional narrowing effect similar to that seen in previous investigations. 26,42 As [Ni] increases (and thus, [Mn] and [Co] decreases) there is a consistent decrease in D due to the signicantly smaller nuclear moment present in Ni, when compared to Mn or Co.…”
Section: Local Lithium Diffusion (Msr)mentioning
confidence: 89%
“…40 Previous investigations on isostructural materials have found the TSH mechanism to occur on a similar timescale (z10 À10 cm 2 s À1 ), but provides a lower activation energy (E a ) diffusion pathway (E TSH a z E ODH a /4). 26 However, the TSH mechanism is only available where [Li] < 1 (due to the requirement for a Li divacancy). In comparison, the C2/m structure has previously been reported to exhibit additional interplanar diffusion pathways between the Li and MO 6 slabs, which may be expected to provide enhanced Li ion conductivity.…”
Section: Local Lithium Diffusion (Msr)mentioning
confidence: 99%
See 2 more Smart Citations
“…A slow decrease was observed from 200 to 500 K due to the motional narrowing of the magnetic environment the muon experienced, commensurate with preceding studies. [ 33,35,36 ] D Li was estimated by employing Equation ().DLi=i=1n1NiZν,isi2νwhere N i is the number of accessible Li + sites in the i th path, Z ν,i is the vacancy fraction of the destination sites, s i is the jump distance between Li + sites, and ν is the fluctuation rate at a given temperature. [ 37 ] Figure shows the electron density map for the hkl (0 1–4) plane along which diffusion occurs in LATP through three steps: 1) fully occupied M1 ( 6b ) to partially occupied M3 ( 36f ), M1→M3; 2) partially occupied M3 ( 36f ) to partially occupied M3 (3 6f ), M3→M3; and 3) partially occupied M3 ( 36f ) to fully occupied M1 ( 6b ) M3→M1.…”
Section: Resultsmentioning
confidence: 99%